The evolution of intracranial aneurysm research from 2012 to 2021: Global productivity and publication trends - Zhang, Qian; Weng, Ling; Li, Jian (Frontiers in Neurology, 2022)
Abstract Background: This study aims to analyze the global research trends and map the knowledge network of intracranial aneurysm (IA) research in recent 10 years. Methods: Publications concerning IA from 2012 to 2021 were retrieved from the Web of Science core collection. Microsoft Excel 2010 and VOSviewer were used to characterize the largest contributors including authors, journals, institutions, and countries. Citespace and VOSviewer were adopted to analyze the trends and knowledge network. Results: A total of 5,406 publications related to IA between 2012 and 2021 were identified, increasing from 344 in 2012 to 762 in 2021. Siddiqui, AH from the USA contributed the most papers. Papers published in World Neurosurgery ranked first in quantity, while Stroke ranked first for total citations and citations per publication. Capital Medical University, Mayo Clinic, and University Department of Neurology Utrecht were the top three prolific institutions. Besides, the USA took the greatest share in the field, and China was almost on par with the USA thanks to rapid growth. Specifically, topics on subarachnoid hemorrhage, endovascular treatment, clipping, vascular disorders, flow diverter, stent, delayed cerebral ischemia, inflammation, and hemodynamics are most frequently covered over the past decade. Conclusions: The contribution made by different countries, institutions, journals, and authors for IA research over the past decade was demonstated in the paper. The main topics include the choice of endovascular treatment or surgical clipping, particularly the application of flow diverter and associated complications, while themes such as the etiopathogenetic features of IA (e.g., inflammation and hemodynamics) deserve more attention.